Complexed Crystal Structure of Saccharomyces cerevisiae Dihydroorotase with Inhibitor 5-Fluoroorotate Reveals a New Binding Mode - Hong-Hsiang Guan; Yen-Hua Huang; En-Shyh Lin; Chun-Jung Chen; Cheng-Yang Huang (Bioinorganic Chemistry and Applications)
Dihydroorotase (DHOase) possesses a binuclear metal center in which two Zn ions are bridged by a posttranslationally carbamylated lysine. DHOase catalyzes the reversible cyclization of N-carbamoyl aspartate (CA-asp) to dihydroorotate (DHO) in the third step of the pathway for the biosynthesis of pyrimidine nucleotides and is an attractive target for potential anticancer and antimalarial chemotherapy. Crystal structures of ligand-bound DHOase show that the flexible loop extends toward the active site when CA-asp is bound (loop-in mode) or moves away from the active site, facilitating the product DHO release (loop-out mode). DHOase binds the product-like inhibitor 5-fluoroorotate (5-FOA) in a similar mode to DHO. In the present study, we report the crystal structure of DHOase from Saccharomyces cerevisiae (ScDHOase) complexed with 5-FOA at 2.5 Å resolution (PDB entry 7CA0). ScDHOase shares structural similarity with Escherichia coli DHOase (EcDHOase). However, our complexed structure revealed that ScDHOase bound 5-FOA differently from EcDHOase. 5-FOA ligated the Zn atoms in the active site of ScDHOase. In addition, 5-FOA bound to ScDHOase through the loop-in mode. We also characterized the binding of 5-FOA to ScDHOase by using the site-directed mutagenesis and fluorescence quenching method. Based on these lines of molecular evidence, we discussed whether these different binding modes are species- or crystallography-dependent.